Zeta Functions, Topology and Quantum Physics - Aoki, Takashi; Kanemitsu, Shigeru; Nakahara, Mikio; Ohno, Yasuo (Developments in Mathematics, 2005)
This volume focuses on various aspects of zeta functions: multiple zeta values, Ohno's relations, the Riemann hypothesis, L-functions, polylogarithms, and their interplay with other disciplines. Eleven articles on recent advances are written by outstanding experts in the above-mentioned fields. Each article starts with an introductory survey leading to the exciting new research developments accomplished by the contributors. This book will become the major standard reference on the recent advances on zeta functions. Audience This book, primarily intended for researchers in number theory and mathematical physics, is also accessible to graduate students in these fields.